Marketing Mix Strategy for Health Services Business: Bibliometric Analysis on Scopus Database - Febby Rosidayani; Qurratul Aini (Future Science, 2024)
Marketing is all the activities and processes that create, communicate, deliver, and offer value to clients, customers, colleagues, and the general public. Hospitals are semi-business healthcare organizations, which deal with marketing. Hospitals must use marketing to address problems and capitalize on opportunities, including the marketing mix. In finding the appropriate and most effective marketing plan to implement, any of the components of the marketing mix can be considered. Marketing has been considered the basis of strategic development in every industry around the world, regardless of whether the organization is engaged in products or services. This study aims to determine the development of marketing mix methods used by healthcare organizations from 2014 to 2023. The method used in this research is quantitative research with a literature study approach - analysis and visualization of literature using VOS viewer software. Data was collected by querying the Scopus database using relevant keywords, namely